ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN DARING DI SMK SE-KECAMATAN KAYUAGUNG - Juai Aptriyana; Neta Dian Lestari; Januardi Januardi (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The problem in this research is how the learning difficulties of students in online learning at SMKs in the Kayuagung District are for the 2020/2021 academic year. The purpose of this study was to determine the learning difficulties of students in online learning at SMK in Kayuagung District. The method used in this study is a qualitative descriptive method.The results showed that the average answer of 99 respondents/students from positive negative questionnaire statements was 72.29% with the category